Situation Report: Poland, 12 October 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Prime Minister Mazowiecki's Inaugural Speech to the Sejm / by Jan de Weydenthal The New Government's Foreign Policy / by Anna Swidlicka Mazowiecki Government Fights to Keep Polish Economy Alive / by Louisa Vinton New Chairman for Poland's Radio and Television Committee / by Roman Stefanowski Trade Unions and Politics in Poland / by Roman Stefanowski The Polish Peasant Party: Problems and Prospects / by Anna Swidlicka Plans for Parliamentary Agricultural Foundation / by Roman Stefanowski Miscellaneous Items / by Roman Stefanowski